How bacterial pathogens avoid phagocyte killing - Areschoug, Thomas (Henry Stewart Talks, 2013)
Background on phagocytic cells, The central role of the macrophage in the immune system, The effectiveness of the neutrophil at killing bacteria, Phagocytosis, Receptor-ligand interactions, Phagosome maturation and intracellular killing, Different types of phagocytosis and phagocytic killing mechanisms, Bacterial mechanisms to evade phagocytosis/phagocytic killing: Evasion of complement-mediated phagocytosis, Evasion of non-opsonic phagocytosis, Targeting of inhibitory receptors, Evasion via T3SS , Increased intracellular survival